FIP bias in a sigmoidal active region. Issue Volume 8:Issue S300(2013) (6th January 2014) - Baker, D.; Brooks, D. H.; Démoulin, P.; van Driel-Gesztelyi, Lidia; Green, L. M.; Steed, K.; Carlyle, J.
Abstract: We investigate first ionization potential (FIP) bias levels in an anemone active region (AR) - coronal hole (CH) complex using an abundance map derived from Hinode /EIS spectra. The detailed, spatially resolved abundance map has a large field of view covering 359″ × 485″. Plasma with high FIP bias, or coronal abundances, is concentrated at the footpoints of the AR loops whereas the surrounding CH has a low FIP bias, ~1, i.e. photospheric abundances. A channel of low FIP bias is located along the AR's main polarity inversion line containing a filament where ongoing flux cancellation is observed, indicating a bald patch magnetic topology characteristic of a sigmoid/flux rope configuration.